What makes us human - United Nations Educational, Scientific; Cultural Organization; Cristina Puerta (The UNESCO Courier, 2024)
Presented in the form of a riddle, this illustrated book by Victor D.O. Santos and Anna Forlati speaks in favour of a diverse and multilingual world. UNESCO has joined forces with publishers around the world to ensure the book is distributed in as many languages as possible.